Lysimachia porcatisepala, a new species of Lysimachia (Primulaceae) from Chongqing, China - Yi, Sirong (Phytotaxa, 2020)
Lysimachia porcatisepala (Primulaceae), a new species is s described and illustrated from Chongqing, China. Morphologically, this new species is similar to L. huangsangensis in calyx lobes with crested veins on the abaxial side, but differs from the latter by the whole plant having sparsely white pubescent, stems erect, corymbose inflorescence with 2–10 flowers, calyx lobes with dense light purple marks outside and glabrous inside, and corolla lobes narrowly ovate and the apex obtuse.